1895 Tenn. Pub. Acts 129-30, An Act to Incorporate the City of South Fulton, in Obion County Tennessee . . . , ch. 85, § 3, pt. 14. - (:unkn) unknown (My University, 1895)
To regulate the storage of gunpowder, tar, pitch, resin, saltpeter, gun cotton, coal oil, and all other combustibles, explosive or inflammable material, and the use of lights, candles, lamps, stove pipes, steam pipes, and chimneys in all storehouses, dwellings, outhouses, shops, stables, and other places, and to regulate and suppress the use and sale of fire crackers or fireworks of all kinds, toy pistols, air guns, or target guns.
Keywords: GUNPOWDER - STORAGE